Anterograde lag screw placement in the posterior column of the acetabulum: A case report and literature review. (February 2022) - Ye, Jialiang; Xie, Liangwen; Liu, Zhongguo; Lin, Jianchun; Yan, Hailan; Chen, Zhikun
Abstract: Acetabular fractures are complex injuries with an annual incidence of approximately 4 per 100, 000 (Laird and Keating, 2005 [1]. Although the open reduction is currently advocated for treating acetabular fractures, some acetabular fractures can be treated by minimally invasive surgery, with the advantages of minor trauma, less bleeding, reduced infection, and shorter operation time. Therefore, we report a case of a patient with a transverse fracture involving the acetabulum treated with a new method of cannulated screw fixation combined with a personalized 3D printed guide to achieving minimally invasive and precise treatment of acetabular fractures while we review the relevant papers. Highlights: Some acetabular fractures can be treated by minimally invasive surgery, with the advantages of minor trauma, less bleeding, reduced infection, and shorter operation time. We report a case of a patient with a transverse fracture involving the acetabulum treated with a new method of cannulated screw fixation combined with a personalized 3D printed guide to achieving minimally invasive and precise treatment of acetabular fractures. Through the new channel of posterior column screw, minimally invasive antegrade screw placement, guided plate assistance, we can complete the operation faster and more conveniently for the benefit of patients.